2019
DOI: 10.3390/ijms20092109
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cannabinoid Receptor Type 1 in Insulin Resistance and Its Biological Implications

Abstract: Endogenous cannabinoids (ECs) are lipid-signaling molecules that specifically bind to cannabinoid receptor types 1 and 2 (CB1R and CB2R) and are highly expressed in central and many peripheral tissues under pathological conditions. Activation of hepatic CB1R is associated with obesity, insulin resistance, and impaired metabolic function, owing to increased energy intake and storage, impaired glucose and lipid metabolism, and enhanced oxidative stress and inflammatory responses. Additionally, blocking periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 112 publications
(149 reference statements)
0
19
0
Order By: Relevance
“…[21][22][23] Furthermore, investigations in both animals and humans have found that cannabinoids have also been connected with type II diabetes and obesity. 26 Cannabinoids and CB1 receptor modulation do, however, influence downstream inflammatory pathways, in particular IL-6 in several tissues. 27,28 Cannabinoid modulates several inflammatory cells, such as gastrointestinal inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Furthermore, investigations in both animals and humans have found that cannabinoids have also been connected with type II diabetes and obesity. 26 Cannabinoids and CB1 receptor modulation do, however, influence downstream inflammatory pathways, in particular IL-6 in several tissues. 27,28 Cannabinoid modulates several inflammatory cells, such as gastrointestinal inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…This is not the first time SCRA have been linked to hyperglycemia (31) or even DKA (32). Given the wide heterogeneity of SCRA and their metabolites, as well as the role of CB 1 in insulin resistance (33), it is possible that some SCRA could lead to DKA in susceptible individuals. Again, without the pathologists report, it is not possible for us to pass comment on our cases, but this is an area that requires further research.…”
Section: Discussionmentioning
confidence: 91%
“…Cannabinoid type 1 receptors (CB1R), an important element of this system, are expressed most densely in the brain but are also present at functionally relevant levels in many peripheral tissues . Research has shown that activation of CB1R increases appetite, insulin resistance, and hepatic lipogenesis, whereas blockade of peripheral CB1R ameliorates obesity and its metabolic consequences . Chronic treatment with rimonabant, the first globally acting CB1R antagonist, has been shown to reduce body weight and improve cardiometabolic risk factors in rats with obesity and humans with overweight/obesity .…”
Section: Resultsmentioning
confidence: 99%